Solving the issue of ensuring the alignment of two intersecting metal wires using a test bench for a metal spraying as an example - D. E. Pisarev; S. I. Mitrokhin; A. I. Starikov (Архитектура, строительство, транспорт)
In this work, the task was to ensure the alignment of two intersecting metal wires to maintain the welding arc at all times. This need arose as a result of an experiment in cold spray metal plating. It revealed a problem that does not allow maintaining a constant spraying process: the welding arc was unstable, because it did not ensure constant contact of differently charged metal wires. A description of the equipment used in the experiment (including both a real prototype and a three-dimensional model) and modifications of the existing mechanism to solve the identified problem is given. Also presented a general view of the modified design, as well as a separated three dimensional model to show the fundamental design changes. As a result, a modified model of the housing, where the welding nozzles are located, has been developed. It is capable to ensure the adjustment of the welding nozzle position and, accordingly, to guarantee constant alignment of the two intersecting metal wires.